Immunogenicity of monoclonal antibody: causes, consequences, and control strategies - Asmani, Ahmad Zafran Amin; Zainuddin, Ahmad Faris Fahmi; Ahmad Azmi Murad, Nadhirah; Mohd Darwis, Nur Hidayati; Suhaimi, Nur Suhaida; Zaini, Erizal; Bakhtiar, M. Taher; Darnis, Deny Susanti; Khotib, Junaidi (Elsevier, 2024)
Antibody-based treatment was first used in 1891 for the treatment of diphtheria. Since then, monoclonal antibodies (mAbs) have been developed to treat many diseases such as cancer and act as vaccines. However, murine-derived therapeutic mAbs were found to be highly immunogenic, and caused anti-drug antibodies (ADAs) reaction, reducing their efficacy and causing severe infusion reactions. Fully human, humanised, and chimeric antibodies were then introduced for better therapeutic efficacy. With the introduction of immune response associated with mAbs immunogenicity. This review explores the immunogenicity of mAbs, its mechanism, contributing factors, and its impact on therapeutic efficacy. It also discusses immunogenicity assessment for preclinical studies and strategies for minimising immunogenicity for effective therapeutic treatment in various diseases. Finally, predicting immunogenicity in drug development is essential for selecting top drug candidates. A lot of methods can be implemented by the researchers and developers to reduce the development of ADAs while simultaneously minimising the immunogenicity reaction of mAbs.